A Survey of Current Practice of Informed Consent in Iranian Hospitals. Issue 3 (3rd July 2018) - Shaker, Seyed Hosein; Hosseini Kasnavieh, Seyed Mohammad; Amini, Milad; Tahmasebi, Ali; Soltani, Siamak
ABSTRACT: Background: Informed consent is legal and ethical process which is considered as important issue in quality of patient's treatment. The aim of the current study was to assess current informed consent of patients admitted in Iranian selected Hospitals, 2016. Materials and Methods: This cross-sectional study was conducted on 2150 patients admitted in 11 public Hospitals. Data was collected using a dichotomous questionnaire with 30 questions. Statistical analysis was done using SPSS software (version 18). Results: The results shown that 46% of patients had medium perception about informed consent, 44% believed to get insufficient information and 66% claimed to have active participation in treatment process. The significant associations were found between some dimensions and important parameters: Understanding of information dimension and education level ( p = 0.008), Participation (in decision-making) dimension and type of hospitalization ( p = 0.01), and level of patients' information dimension with resident address ( p = 0.027) and medical specialty ( p < 0.001). Conclusion: In our study the current informed consent of patients wasn't in desirable condition. The Necessary measures are required to achieve a level that the patients' informed consent convert to informed choices. Hospital healthcare team need to take proper actions such as give proper information, patient training, sufficient information and etc.